Fragment-based discovery of DNA gyrase inhibitors targeting the ATPase subunit of GyrB. Issue 4 (15th February 2016) - Mesleh, Michael F.; Cross, Jason B.; Zhang, Jing; Kahmann, Jan; Andersen, Ole A.; Barker, John; Cheng, Robert K.; Felicetti, Brunella; Wood, Michael; Hadfield, Andrea T.; Scheich, Christoph; Moy, Terence I.; et al.
Graphical abstract: Abstract: Inhibitors of the ATPase function of bacterial DNA gyrase, located in the GyrB subunit and its related ParE subunit in topoisomerase IV, have demonstrated antibacterial activity. In this study we describe an NMR fragment-based screening effort targeting Staphylococcus aureus GyrB that identified several attractive and novel starting points with good ligand efficiency. Fragment hits were further characterized using NMR binding studies against full-length S. aureus GyrB and Escherichia coli ParE. X-ray co-crystal structures of select fragment hits confirmed binding and suggested a path for medicinal chemistry optimization. The identification, characterization, and elaboration of one of these fragment series to a 0.265 μM inhibitor is described herein.